ANALYSIS OF TAX KNOWLEDGE, TAX SANCTIONS AND SYSTEM MODERNIZATION ON MSME TAXPAYER COMPLIANCE - Cincin Ayu Wulandari; Yuwita Ariessa Pravasanti; Sri Laksmi Pardanawati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The purpose of this study is to determine the compliance of MSME taxpayers in Karanganyar with variables such as: tax knowledge, tax sanctions, and system modernization. The research population is 19,355 taxpayers registered at KPP Pratama Karanganyar. The sampling technique in this study was random sampling with multiple linear regression analysis models. The results of the study, tax knowledge and system modernization have an effect on MSME taxpayer compliance in Karangayar City while tax sanctions have no effect on MSME taxpayer compliance in Karanganyar City. Suggestions in this study include: KPP Pratama Karanganyar as a state institution is expected to evaluate and improve services and policies in the future, especially those related to taxpayers. In future research, more varied variables can be used. And as the development of science is expected to use more accurate research methods.